In Vitro Antioxidant, Anti-inflammatory, and In Vivo Anticolitis Effects of Combretin A and Combretin B on Dextran Sodium Sulfate-Induced Ulcerative Colitis in Mice - Mbiantcha Marius; Dawe Amadou; Atsamo Albert Donatien; Ateufack Gilbert; Yousseu Nana William; Khalid Rauf; Mehreen Arif; Fanta Yadang Sabine Adeline; Njoku Isaac Saint; Hamza Dar; Naeem Ur Rehman; Izhar Ahmad (Gastroenterology Research and Practice)
Combretum fragrans (Combretaceae) is a Cameroonian medicinal plant containing various secondary metabolites and traditionally used for the treatment of several pathologies. Two cycloartane-type triterpenes, Combretin A and Combretin B, were isolated from this plant. This study was aimed at evaluating the anti-inflammatory, antioxidant, and anticolitis effects of these compounds. In vitro anti-inflammatory properties were evaluated by inhibition of cyclooxygenase, 5-lipoxygenase, and denaturation of the protein; antioxidant properties were assessed by using 1,1-diphenyl-2-picrylhydrazyl (DPPH), (2,2’-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid)) ABTS•+, capacity tests ferric reducing antioxidant (FRAP), and trapping nitric oxide. For in vivo analysis, we used the model of ulcerative colitis induced by Dextran Sulfate Sodium (DSS). Studies of the anti-inflammatory activity showed that Combretin A and Combretin B had maximal inhibitory activity on cyclooxygenase (71.92% and 89.59%), 5-lipoxygenase (76.68% and 91.21%), and protein denaturation (63.93% and 87.78%). Antioxidant activity on DPPH, ABTS•+, ferric reducing antioxidant capacity (FRAP), and nitric oxide scavenging showed that Combretin A and Combretin B showed good antioxidant activities. These compounds significantly reduced the signs of DSS-induced colitis in the treated animals by preventing the weight loss of the animals, by significantly reducing the disease activity index, improving the condition of the stool, preventing the reduction of the length of the colon, and preventing the degradation of the colon. This study revealed that Combretin A and Combretin B have anti-inflammatory, antioxidant, and curative properties against colitis experimentally induced by DSS in rats.